2014
DOI: 10.4172/2157-7099.1000229
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Approach to the Diagnosis of Adenocarcinoma of the Lung

Abstract: Introduction: Differentiation between adenocarcinoma of the lung (LADC) from the other non-small cell lung carcinoma (NSCLC) is possible by immunohistochemistry. When diagnosis of LADC is established, the rest of lung cancer tissue could be used for molecular testings, particularly EGFR analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In one of our studies, we found that TTF-1 was expressed in 85.2% and in the other study, in 86% of lung adenocarcinomas [12,33]. We also found that TTF-1 was also expressed in benign lung tumors [34,35].…”
Section: Thyroid Transcription Factor-1 (Ttf-1)supporting
confidence: 67%
“…In one of our studies, we found that TTF-1 was expressed in 85.2% and in the other study, in 86% of lung adenocarcinomas [12,33]. We also found that TTF-1 was also expressed in benign lung tumors [34,35].…”
Section: Thyroid Transcription Factor-1 (Ttf-1)supporting
confidence: 67%